A case of antiepiligrin cicatricial pemphigoid with extensive cutaneous erosions mimicking pemphigus vulgaris. (21st June 2018) - Suvirya, Swastika; Pathania, Sucheta; Malhotra, Kiran Preet; Verma, Parul
Abstract : Cicatricial pemphigoid (CP) is a chronic, autoimmune, subepidermal blistering disease with predominant mucosal involvement. In this article, we report a young patient with mucosal and extensive cutaneous involvement in the form of large erosions mimicking those of pemphigus vulgaris thus leading to diagnostic dilemma. We were unable to find any other previous reports with such extensive cutaneous erosions mimicking those of pemphigus vulgaris. Laminin 5 was the antigen found on knockout substrate testing. Antiepiligrin CP is a distinct subtype of CP with antibodies against laminin 5. This subtype is mostly associated with malignancy but no underlying malignancy was found in our case. Present report also highlights the importance of knockout substrate testing when immunoblot is not available.